Результати та перспективи досліджень османських пам’яток Північного Причорномор’я - Біляєва, С.О. (Археологія і давня історія України, 2010)
Статтю присвячено огляду результатів авторських
історико-археологічних досліджень пам’яток
османського періоду Північного Причорномор’я,
їх значення для формування нового бачення міжкультурних стосунків східнослов’янського та близькосхідного
світів. Запропоновані перспективні напрямки подальшого вивчення проблематики. The interest toward the Ottoman archaeology has
been increased in the World science and in the Ukraine
apparently at the end of 20th century.
In the course of the excavation in Ochakiv, including
the international part of expeditions in 1997—1998 year,
the new facts of its historical development were obtained.
Among these discoveries are: more early date of the formation
of the site, the historical and chronological periodization
of the cities structure, collection of unique artifacts.
The international and interdisciplinary projects at
Akkerman fortress were provided in 1999—2009 yy.
also. The great part of investigations was carrying out
on the base of undestructing archaeology with the using
of the new equipment. The importand results were
obtained in the course of the excavation of the Ottoman
bath house and barbican and building periodisation of
the fortification was established. The mode of life was
represented by variable collection of artifacts.
The perspectives of the study of the Ottoman monuments
of the Black Sea area take the great significance
for decision of problems of the Ukrainian and Turks
interrelations.